Short-time Work Subsidies in a Matching Model - Volker Meier (Center for Economic Studies and ifo Institute (CESifo), 2018)
We consider positive and normative aspects of subsidizing work arrangements where subsidies are paid in time of low demand and reduced working hours so as to stabilize workers' income. In a matching framework such an arrangement increases labor demand. Tightening eligibility to short-time work benefits tends to reduce the wage while the impact on unemployment remains ambiguous. We develop a modified Hosios condition characterizing an efficient combination of labor market tightness and short-time benefit loss rate.
Keywords: E24; H24; J41; J63; J64; 330; short-time work; unemployment insurance; employment subsidies